The youth life projects of Alto do Tamanduá / AL / Os projetos de vida dos jovens do Alto do Tamanduá/AL - Erick da Silva Menezes; Francisco Carlos de Lucena (Universidade Estadual de Alagoas, 2016)
The survey was conducted in maroon comunidade quilombola Alto do Tamanduá and settlement Santa Vitoria in the Poço das Trincheiras / AL. The municipality is located in the hinterland, far 216 km from Maceió, the state capital. The overall objective of the research is to explain how the individual projects of life of young people in these communities are built. We use unstructured interviews and ethnography. They were conducted 23 interviews with young people from the two communities aged between 15 and 25 years. Overall, young people design their lives out of the communities, since the possibilities are restricted. Young people put education as a potential possibility of social and career advancement. The land is seen as a determining factor for young people to project their lives in the field, however, this factor is quite restricted in quilombo, as most families do not have land tenure, while the settlement all families have a lot with 15 hectares. The countryside is valued as a space "quiet" and "peaceful". The city is seen as the seat of jobs and opportunities, but also of violence and a lot of "agitation"